1802 CAPSTONE: an observational retrospective analysis comparing a complement activation multianalyte panel vs. Standard ANA testing: systemic lupus erythematosus diagnosis, treatment outcomes and economic impact. (14th December 2022) - O'Malley, Tyler; Xie, Fenglong; Su, Yujie; Clinton, Cassie; Zack, Debra J; Haechung, Chung; Grabner, Michael; Curtis, Jeffrey R
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a complex clinical disease that often takes years and repeated testing to adequately diagnose. Standard biomarkers have low specificity (ANA) or low sensitivity (anti-dsDNA, anti-Smith). The advent of a multianalyte assay panel (MAP) incorporating innovative cell-bound complement activation markers warrants comparison of its clinical utility to conventional autoantibodies for the diagnosis and treatment of SLE. Objective: This study compares the likelihood of SLE diagnosis, SLE treatment initiation, and the downstream impact on healthcare utilization on over 40, 000 patients tested with either MAP (AVISE Lupus) versus standard of care lab testing with traditional anti-nuclear antibody (ANA) testing strategy cohort (tANA). Methods: Using electronic health record (EHR) data from the Illumination Health registry (an integrated EHR record database encompassing records from over 300 US rheumatologists), an observational retrospective cohort study was performed. Health records from 01/2016 to 12/2020 and administrative claims with cost data for a subset of patients linkable to the HealthCore Integrated Research Database (HIRD) and Medicare data were analyzed. Two cohorts were established: MAP testing strategy and the tANA approach. Each test result was classified as positive, negative, or indeterminate and outcomes were stratified based on test results. Multivariable logistic regression was used to estimate odds ratios (OR) comparing the likelihood of SLE medication initiation and SLE diagnosis between the MAP and tANA cohorts. Test impact on SLE diagnosis, treatment initiation, patterns of repeat testing, and downstream healthcare utilization were analyzed. Results: 21, 827 MAP testing episodes and 22, 778 tANA testing episodes were included in the main cohort. Findings include: 2, 437 (11.2%) patients tested positive by MAP compared to 5, 364 (23.6%) of tANA(+) patients. MAP(+) patients were over 5-fold more likely to be diagnosed with SLE as compared to the tANA patients, 31% vs. 8% (OR = 5.11, 95% CI 4.43-5.89). Similarly, the new patient cohort was 6-fold more likely to achieve an SLE diagnosis when MAP is used, 30% vs. 6% (OR = 6.34, 95% CI 5.12- 7.86). Among patients with no baseline prescription for SLE medication(s), MAP(+) patients were more likely to initiate SLE medications compared to tANA(+) (43% vs. 32%, OR = 1.57, 95% CI 1.41-1.76). In patients new to the practice within the preceding year, the treatment effect was even larger 55% vs. 33% (adjusted OR = 2.77, 95% CI 2.31-3.32). Repeated testing was 3.5 times higher in tANA tested patients than in those tested with MAP. Linked EHR-Medicare data revealed a greater decrease in post-test vs. pre-test mean annualized outpatient lab testing in MAP(-) (-985, p < 0.0001) vs. tANA(-) (-356, p<0.0001) patients. A similar analysis of outpatient lab testing in EHR-HealthCore linked data revealed similar numerical trends but did not reach significance (p > 0.05). Conclusions: The significantly greater likelihood of SLE diagnosis and SLE medication initiation in MAP(+) vs. tANA(+) patients is consistent with improved clinical actionability, potentially shortening time to diagnosis. MAP(-) patients experienced a greater decrease in outpatient lab testing post-test relative to tANA(-) patients, supporting the improved negative predictive value of MAP vs. tANA, and MAP patients were tested 3.5 fewer times than tANA patients, reducing valuable health-care dollars.